Sacred and secular religion and politics worldwide - Norris, Pippa; Inglehart, Ronald (Cambridge ; New York : Cambridge University Press, 2011)
"This book develops a theory of secularization and existential security, demonstrating that the publics of virtually all advanced industrial societies have been moving toward more secular orientations during the past fifty years, but also that the world as a whole now has more people with traditional religious views than ever before"--
"Seminal nineteenth-century thinkers predicted that religion would gradually fade in importance with the emergence of industrial society. The belief that religion was dying became the conventional wisdom in the social sciences during most of the twentieth century. The traditional secularization thesis needs updating, however, religion has not disappeared and is unlikely to do so. Nevertheless, the concept of secularization captures an important part of what is going on. This book develops a theory of existential security. It demonstrates that the publics of virtually all advanced industrial societies have been moving toward more secular orientations during the past half century, but also that the world as a whole now has more people with traditional religious views than ever before. This second edition expands the theory and provides new and updated evidence from a broad perspective and in a wide range of countries. This confirms that religiosity persists most strongly among vulnerable populations, especially in poorer nations and in failed states. Conversely, a systematic erosion of religious practices, values, and beliefs has occurred among the more prosperous strata in rich nations"--
Machine generated contents note: Part I: Understanding Secularization: 1. The secularization debate; 2. Measuring secularization; 3. Comparing secularization worldwide; Part II: Case Studies of Religion and Politics: 4. The puzzle of secularization in the United States and Western Europe; 5. A religious revival in post-communist Europe?; 6. Religion and politics in the Muslim world; Part III: The Consequences of Secularization: 7. Religion, the Protestant ethic, and moral values; 8. Religious organizations and social capital; 9. Religious parties and electoral behavior; Part IV: Conclusions: 10. Secularization and its consequences; 11. Re-examining the theory of existential security; 12. Re-examining evidence for the security thesis.
Includes bibliographical references (p. 331-358) and index.
Description based on print version record.
Keywords: Religion and politics; Secularism; POLITICAL SCIENCE / General; SOCIAL SCIENCE / Sociology of Religion; Electronic books